Integral Assessment of the Regional Environmental Management Effectiveness - A. I. Beloysov; E. V. Zakalyukina (Наука. Инновации. Технологии)
Introduction: Considering all the growing trends associated with the deterioration of the natural environment, the priorities, inherent in the sustainable development model, are shifting towards the long-term preservation of the biosphere and natural potential. The key direction for this task implementation should be processes aimed at the development of resource conservation of natural assets. Materials and methods of the research: To assess the conjugation of production and degradation processes, it is proposed to use the contingency coefficient, which takes into account the multidirectional nature of these processes. The peculiarity of the connection between production processes with environmental and resource-saving parameters has been identified and presented in a graphical form. The results of the study and their discussion: The generalized research results show that the most accurate and effective for assessing the innate quality of natural resources is a multi-stage approach with elements of the predicted productivity of the i-th natural resource. The model of the productivity balance proposed by the authors allows to determine the change in the level of land productivity in order to prevent degradation processes. Conclusions: The calculations carried out in the research using the balance of nutrients showed a deficiency of nutritional chemicals in the soils of the Stavropol Territory. The authors concluded that to determine the type of nature management existing in a territorial entity, it is advisable to use the coefficient of environmental threat, applying it taking into account the peculiarities of ecological zoning.